(untitled) (Web of Teachers: Inderscience Research, 2026)
The rapid integration of artificial intelligence (AI) technologies is reshaping educational landscapes worldwide, with significant implications for foreign language education in emerging economies. This review article examines the integration of AI-driven technologies in English as a Foreign Language (EFL) and broader foreign language education within the higher education systems of Uzbekistan and Kazakhstan, framed within the context of Sustainable Development. Drawing upon a synthesis of peer-reviewed literature published between 2021 and 2026, this article evaluates the pedagogical potential of tools such as ChatGPT, Grammarly, Duolingo Max, adaptive learning platforms, and AI-powered speech recognition systems. The review highlights how these technologies foster learner autonomy, communicative competence, and personalized learning, while also addressing critical challenges including the digital divide, ethical considerations, academic integrity, and teacher preparedness. Comparatively analyzing national digitalization policies and AI implementation initiatives in both countries, the article argues that sustainable AI integration requires coordinated investment in infrastructure, teacher professional development, and ethical governance frameworks. The findings carry substantial implications for policymakers, curriculum designers, and language educators across Central Asia.